2015
DOI: 10.1007/s13277-015-4221-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HPV16 E6/E7 mediated HIF-1α upregulation of GLUT1 expression in lung cancer cells

Abstract: High-risk human papillomavirus (HPV) infection may play an important role in non-small cell lung carcinoma (NSCLC) development. However, some recent studies have proved that it was not directly associated with lung cancer. The aim of this study was to evaluate the underlying molecular mechanism that HPV16 regulate the expression of GLUT1 and may promote the development of lung cancer. HPV16, HIF-1α, and GLUT1 were detected in pleural effusions of patients with lung cancer (n = 95) and with benign lung disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 39 publications
1
69
0
Order By: Relevance
“…GLUT1 is a glucose transporter that as the glucose influx into a cell is the first rate-limiting process involved in glucose metabolism. 16,17 HKII is a key enzyme that catalyzes the first step in the glycolysis pathway. 18,19 These two enzymes are key enzymes in the regulation of cellular glycolysis and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1 is a glucose transporter that as the glucose influx into a cell is the first rate-limiting process involved in glucose metabolism. 16,17 HKII is a key enzyme that catalyzes the first step in the glycolysis pathway. 18,19 These two enzymes are key enzymes in the regulation of cellular glycolysis and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigated the association between glucose transporter 1 (GLUT1) and various tumor types, and identified that the abnormal expression of GLUT1 and other relevant genes may be associated with the intensive glucose metabolism in malignant cells (18). Previous studies have demonstrated that the transcription of GLUT1 is enhanced by HIF-1α in other solid types of cancer under hypoxic conditions (19,20), and glycolysis is enhanced to compensate for the increased energy demands (21,22). Therefore, HIF-1α and GLUT1 may also be associated with the regulation of certain oncogenes and growth factors in GC.…”
Section: Introductionmentioning
confidence: 99%
“…The screening of lung cancer cell lines Based on our previous results, H1299 cell line was low E6 and E7 expression cell line, and A549 cell line was high E6 and E7 expression cell line [21]. The expression of KIF7 was screened in normal bronchial epithelial cell line HBE and lung cancer lines H1299, H460, and A549, respectively.…”
Section: Resultsmentioning
confidence: 99%